Feasibility study for D-lactic acid production from thai rice by Leuconostoc pseudomesenteroides TC49 and D-lactic acid purification - Tasneem Chemama (2020)
© 2020, Chiang Mai University. All rights reserved. Two enantiomers of lactic acid, D- and L-forms, are naturally produced by lactic acid bacteria. Generally, L-lactic acid is more abundant than D-lactic acid. Both forms have been importantly used as monomers in bio-plastic industry. In this study, total of 251 lactic acid bacterial strains were isolated and screened from samples collected in southern and northern Thailand. Among these bacteria, only 7 isolates produced D-lactic acid with optical purity ranging from 96.2 to 99.7%. The isolate TC49, identified as Leuconostoc pseudomesenteroides, produced the highest D-lactic acid and was selected for further investigation. When Thai broken rice was used as a raw material for D-lactic acid fermentation by the selected strain, D-lactic acid yield and productivity were 93 ± 0.03 g/l and 1.29 g/l/h, respectively, under the optimal conditions. Upon further recovery and purification by the ultrasonic extraction process, D-lactic acid obtained was 99% optical purity and was structurally examined by 1H-NMR determination. The results indicated the high potential of Leu. pseudomesenteroides TC49 as a D-lactic acid producing strain using rice as a raw material.